Real-time analysis of initiation regulation systems during the progression of the reconstituted chromosomal replication cycle - Koki Kanoh; Masayuki Su’etsugu (Scientific Reports)
Abstract Chromosome replication in Escherichia coli is primarily regulated at the initiation stage, where the DnaA protein activates replication at the chromosomal origin, oriC. Both DnaA and oriC undergo feedback regulation based on replication progression. Previously, we reconstituted the entire replication cycle using 26 purified proteins in a system termed replication cycle reaction (RCR). This system enables the exponential propagation of oriC circular DNA through autonomous replication cycles. In this study, we integrated regulatory mechanisms into the RCR and analyzed their effects on DNA propagation using real-time detection. The oriC sequestration system involves SeqA binding to hemimethylated oriC—generated during nascent DNA synthesis to prevent reinitiation. SeqA inhibited RCR, but the addition of Dam methylase relieved this inhibition. In the DnaA regulation system, active ATP-DnaA is inactivated by Hda in association with the DNA-loaded clamp, converting it to ADP-DnaA. Reactivation occurs through nucleotide exchange facilitated by the DnaA-reactivating sequence (DARS). Hda suppressed replication in RCR, while DARS restored activity. These results demonstrate that regulatory mechanisms controlling replication initiation in the RCR system faithfully replicate the cell cycle regulation of chromosome replication observed in vivo.